RETRACTED: Sturgen diseases risks in closed water supply facilities and possible approaches to pharmacotherapy and prevention - Basankina Viktoriya; Kaloshkina Inna; Basankin Aleksey; Semenenko Marina; Semenenko Ksenia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001